Implementation of Education Management Standards in Senior High School - Neliwati, Neliwati; Daulay, Isma Hayati; Sulasmi, Sulasmi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study describes the implementation of education management standards at Madrasah Aliyah Darul Ihsan Selemak Village, Deli Serdang, North Sumatra. The focus of his research is on educational planning, which includes the vision, mission, and goals of the school, the implementation of education by the school's academic calendar, school supervision carried out by the head and deputy principals, as well as evaluation of education as an effort to improve the quality of education. This study used qualitative research methods. The data obtained in the study came from school principals, deputy principals, TU heads, and teachers who teach at the school. Observation, interviews, and documentation do data collection. The sources of this research are primary and secondary; the stages of analysis in this qualitative research are data collection, data reduction and categorization, data appearance, and conclusion—guarantees for data validity, namely credibility, transferability, dependability, certainty, and triangulation. The results of the research study show that educational planning at Madrasah Aliyah Darul Ihsan is by the standards of education management because it includes the vision, mission, and goals as well as work plans at the madrasa. However, several notes need to be considered, namely, the need to be improved to implement the school's goals. Education management standards carry out an educational evaluation at Madrasah Aliyah Darul Ihsan.